Downregulation of tRNA methyltransferase FTSJ1 by PM2.5 promotes glycolysis and malignancy of NSCLC via facilitating PGK1 expression and translation - Yiling Wang; Yuxin Wen; Qianqian Chen; Yongyi Huang; Duanyang Zhou; Wenhan Yang; Lin Yang; Juan Xiong; Kaiping Gao; Liyuan Sun; Rihong Zhai (Cell Death and Disease)
Abstract Fine particulate matter (PM2.5) exposure has been associated with increased incidence and mortality of lung cancer. However, the molecular mechanisms underlying PM2.5 carcinogenicity remain incompletely understood. Here, we identified that PM2.5 suppressed the expression of tRNA methyltransferase FTSJ1 and Am modification level of tRNA in vitro and in vivo. FTSJ1 downregulation enhanced glycolytic metabolism of non-small cell lung cancer (NSCLC) cells, as indicated by increased levels of lactate, pyruvate, and extracellular acidification rate (ECAR). Whereas treatment with glycolytic inhibitor 2-DG reversed this effect. In contrast, upregulation of FTSJ1 significantly suppressed glycolysis of NSCLC cells. Mechanistically, the silencing of FTSJ1 increased NSCLC cell proliferation and glycolysis through enhancing the expression and translation of PGK1. In human NSCLC tumor samples, FTSJ1 expression was negatively correlated with PGK1 expression level and the SUVmax value of PET/CT scan. In summary, our work reveals a previously unrecognized function of PM2.5-downregulated FTSJ1 on PGK1-mediated glycolysis in NSCLC, suggesting that targeted upregulation of FTSJ1 may represent a potential therapeutic strategy for NSCLC.